High-quality images on a two-piece metal can - Huang, Yih-ping (Computers in industry, 1992)
To generate high-quality distorted images for a two-piece metal can, one needs not only a proper mapping technique and an understanding of the deforming behavior of the surface of a can in formation, but also must realize the limitations that exist in this type of image generation process. The deformation characteristics of the surface of a can are key elements in the numerical simulation in image processing and are functions of many factors, such as the size of a can, material properties, can thickness, the drawing machine used, and drawing conditions. It is still hard to find a unique, all encompassing mathematical model for describing these deformation characteristics. This study performs limited experimental tests, and from the data helps to characterize the distortion behavior of cans of different sizes. These behaviors can be illustrated and compared by means of the graphical display images provided herein. Also several equations are introduced to described the images. Setting the proper resolution for a data image often depends on the reliability of available input and output devices. Detailed discussion on this subject is included. The constrained average thresholding method is used to enable the use of a higher-resolution generated image on a can. This would be theoretically impossible using a traditional process.